Role of microRNAs in non-functioning pituitary adenoma - Rajani, Mehak; Yumna Mirza; Rohan Advani; Syed Muhammad Adnan Ali; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Non-functioning pituitary adenomas account for 30% of anterior pituitary tumours. Based on their inability to secrete hormones, these are often diagnosed incidentally or due to pressure symptoms. Understanding the pathogenesis of these adenomas can provide insight into factors leading to its progression and serving as biomarkers for early recognition. A literature search was performed in the current narrative review for articles published in PubMed for the last 10 years till January 2020 on micro-ribonucleic acid involved in the pathogenesis of non-functioning pituitary adenomas. Of the 478 articles found, 21(4.4%) were filtered. In total, 106 micro-ribonucleic acids were identified, 25(23.5%) of which appeared in more than one study. Among them, 7(28%)were up-regulated, 11(44%) down-regulated, and 7(28%) were either up- or down-regulated. Micro- ribonucleic acids allow the screening, diagnosis and treatment of diseases in a relatively easy and inexpensive manner. Continuous...